Problematics of Economic Education at SMA Negeri 1 Batang Gasan: A Literature Review - Roza, Silvia; Novitri, Rina (The Future of Education Journal, 2026)
Economics education at the senior high school (SMA) level plays a crucial role in developing students' rational thinking skills and economic literacy. However, various studies indicate that economics learning still faces a number of challenges, both in terms of learning methods, learning motivation, and students' economic literacy. This study aims to examine the challenges of economics education through a literature review approach, focusing on the context of SMA Negeri 1 Batang Gasan. The method used was a literature review of journal articles and relevant research published between 2022 and 2025. The results of the study indicate that economics learning is still dominated by conventional methods, low student motivation and economic literacy, and a lack of connection between the material and real life. These findings are expected to form the basis for developing more contextual and innovative economics learning.